Methods and tools for evaluating strategy performance in construction company management - Pereli, D.; Koval, I.; Kryvushchenko, S.; Gega, S. (Ways to Improve Construction Efficiency, 2024)
Evaluating the performance of strategies in construction company management is a key factor in enhancing their competitiveness, sustainability, and operational efficiency in the context of the rapidly evolving construction services market. Strategic decisions made at the management level directly influence project implementation, resource utilization, financial performance, and the quality of construction works. In the contemporary environment of globalization and digitalization in the construction industry, there is a need for a comprehensive approach to assessing strategy performance, which includes the use of quantitative and qualitative analysis methods, integration of digital platforms, and managerial analytics tools. Particular attention is given to the combination of traditional performance indicators, such as financial results, adherence to deadlines, and cost control, with indicators of strategic development: innovation activity, implementation of digital solutions, stakeholder satisfaction levels, and the efficiency of internal processes. The use of Balanced Scorecard (BSC) methods, KPI dashboards, scenario analysis, and Business Intelligence systems enables the evaluation of company performance across different management levels, forecasting deviations, and timely strategy adjustments. A critical aspect is the integration of modern digital technologies, such as ERP systems, financial analysis modules, and data analytics tools, which allow for automated data collection, increased process transparency, and rapid response to changes in the external environment. The combination of these approaches forms a unified system for monitoring strategy effectiveness, ensuring flexibility in decision-making and maximizing outcomes. Comprehensive analysis of strategy performance allows the identification of key success drivers, evaluation of risks, and assessment of optimization potential for managerial decisions.